The Economics of Self-Employment and Entrepreneurship - Parker, Simon C. (Cambridge University Press, 2004)
As self-employment and entrepreneurship become increasingly important in our modern economies, Simon C. Parker provides a timely, definitive and comprehensive overview of the field. In this book he brings together and assesses the large and disparate literature on these subjects and provides an up-to-date overview of new research findings. Key issues addressed include: the impact of ability, risk, personal characteristics and the macroeconomy on entrepreneurship; issues involved in raising finance for entrepreneurial ventures, with an emphasis on the market failures that can arise as a consequence of asymmetric information; the job creation performance of the self-employed; the growth, innovation and exit behaviour of new ventures and small firms; and the appropriate role for governments interested in promoting self-employment and entrepreneurship. This book will serve as an essential reference guide to researchers, students and teachers of entrepreneurship in economics, business and management and other related disciplines.